Refractive status of medical students of Mymensingh Medical College - Akhanda, AH; Quayum, MA; Siddiqui, NI; Hossain, MM (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):493-6 The abstract of this article is available on the PubMed website